Growth, maturity and mortality of Upeneus sulphureus from Andhra-Orissa coast - Reuben, S; Vijayakumaran, K; Chittibabu, K (Indian Journal of Fisheries, 2011)
Visakhapatnam Research Centre, Central Marine Fisheries Research InstituteAr/dhra University PO, Visakhapatnam, Andhra Pradesh 530 003